Empirical Evidence of Blended Learning in Indonesian EFL Class - Sebastianus Menggo; Hieronimus Canggung Darong (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
Blended learning necessitates a digitization technology on the part of both instructors and students, the use of up-to-date instructional strategies, adaptable learning procedures, the efficiency of the processes, space, and financial resources, as well as learner motivation and independence; all of these factors lead to a rise in learner academic achievement. Unfortunately, the results ofthe most recent empirical studies do not support the idea that blended learning help learners enhance their English proficiency and their level of learning independence. There is proof that blended learning impacts the English proficiency, learning independence, enthusiasm, and ICT skills of students. This article analyzed and quantified the effectiveness of blended learning in English as a Foreign Language (EFL). This study is a quantitative explanatory research type with a pre-test and post-test design. One hundred eighty students from the Agronomy Study Program at Universitas Katolik Indonesia Santu Paulus Ruteng participated in the study. A method of random sampling was utilized, and from that population, 73 participants were selected as samples. Data was taken by test and non test, then analyzed by a software program called SPSS 22.0. Teen blended learning sessions, including five face-to-face and five virtual sessions, are conducted using the Zoom platform. The findings indicate that students' English language skills improve with blended learning (the mean score on the posttest was 82.57), as do their levels of learning independence (82.44%), learning enthusiasm (76%), and ICT skills (70.43%).